Percepción sobre el cuidado y acompañamiento en familiares de pacientes con enfermedad oncológica en el municipio de Quimbaya, Quindío - López Murillo, Natalia (Universidad Antonio Nariño, 2023)
The present research work seeks to know the perception of care and accompaniment of family caregivers of patients with oncological disease in the municipality of Quimbaya, Quindío.